Differential proteomics analysis of bile between gangrenous cholecystitis and chronic cholecystitis. (December 2018) - Wang, Linjie; Sun, Wei; Chang, Yingbin; Yi, Zhenghui
Abstract: To establish human biliary protein expression profiles of gangrenous cholecystitis, chronic cholecystitis, and to discover differently expressed proteins for gangrenous cholecystitis by comparative proteomics, we gathered human gallbladder bile samples from gangrenous cholecystitis and chronic cholecystitis patients, respectively After removing the bile salts and lipid peptide fragments were identified by the iTRAQ-coupled LC-MS/MS technology, then identified in SwissProt with Mascot software. A total of 2251 proteins from chronic cholecystitis patients and 2180 proteins from gangrenous cholecystitis patients were identified. A total of 575 differential proteins were found between gangrenous cholecystitis and chronic cholecystitis, 159 proteins were over-expressed and 416 proteins were under-expressed in gangrenous cholecystitis. By bio-informatics analysis, in gangrenous cholecystitis, cell death, necrosis, immune response of neutrophils, apoptosis and degranulation of cells were activated; while cell survival, fatty acid metabolism, transport of molecular and proliferation of cells were inhibited, which might reflect the de-compensatory phase. Pathway analysis showed acute phase proteins were changed, indicating the role of the inflammatory response in the pathogenesis of gangrenous cholecystitis. Six acute phase proteins were found up-regulated, implying a close linkage to gangrenous gallbladder. Our study could be applicable in the biomarker discovery of gangrenous cholecystitis.